The Promise of Trinitarian Theology Theologians in Dialogue with T.F. Torrance. - Colyer, Elmer M. (Lanham : Rowman & Littlefield Publishers, 2001)
Thomas F. Torrance is considered by many to be the most outstanding living Reformed theologian in the Anglo-Saxon world. In The Promise of Trinitarian Theology, Elmer M. Colyer presents a collection of essays critiquing Torrance's work. It explores his place in Reformed theology and his relation to the Greek fathers. Both everyday life and scientific understanding are discussed in the essays within. The Promise of Trinitarian Theology is a hopeful step engaging the works of T.F. Torrance and the theology behind his words.
Scientific Discovery as a Form of RevelationHuman Science and Cosmic Light; The Mobility of Angels; Notes; Chapter 11 -- Natural Science and Christian Faith in the Thought of T.F. Torrance; Charting the Relationship of Science and Theology; Formal Methodological Parallels; Common Material Interests; Overlapping Historical Development; Torrance's Achievement; Notes; Chapter 12 -- Thomas Torrance Responds; David Torrance; Alasdair Heron; Andrew Purves; Gary W. Deddo; Colin Gunton; George Hunsinger; Ray Anderson; Kurt Richardson; Elmer M. Colyer; Chris Kaiser; Mark Achtemeier; Notes.
Thomas F. Torrance's Major Publications.
Description based on print version record.
Keywords: Trinity; Torrance, Thomas F. -- 1913-2007.; Theology, Doctrinal -- History -- 20th century; Trinity -- History of doctrines -- 20th century; Religion and science -- History -- 20th century; RELIGION / Christian Theology / General; Electronic books